La communauté homosexuelle [1956] - Maurice Leznoff; William A. Westley (Genre, Sexualité et Société)
This article, based on a survey done in a large city in Canada during the first half of the 1950s, describes the organization of the "homosexual community" with particular emphasis on the crucial division between homosexuals who do not care about demonstrating their sexual orientation and those who seek to conceal it carefully, avoiding the first group in so doing. It shows in particular that known homosexuals are also those belonging to the most modest occupational categories.